Exploration of the Role of m6 A RNA Methylation Regulators in Malignant Progression and Clinical Prognosis of Ovarian Cancer - Wei, Qinglv; Yang, Dan; Liu, Xiaoyi; Zhao, Hongyan; Yang, Yu; Xu, Jing; Liu, Tao; Yi, Ping (Frontiers in Genetics, 2021)
Ovarian cancer is the most deadly gynecologic malignancy worldwide. It is warranted to dissect the underlying mechanisms and identify the critical gene regulatory network in ovarian cancer. N6-methyladenosine (m6A) RNA methylation, as the most prevalent RNA modification, is orchestrated by the m6A RNA methylation regulators and has been implicated in malignant progression of various cancers. In this study, we comprehensively investigated the genetic landscape and expression profile of the m6A RNA methylation regulators in ovarian cancer and found that multiple m6A RNA methylation regulators are frequently amplified and up-regulated in ovarian cancer. Utilizing consensus cluster analysis, we stratified ovarian cancer samples into four clusters with distinct m6A methylation patterns and patients in these subgroups displayed the different clinical outcomes. These four clusters of ovarian cancer were subject to different tumor microenvironment (TME) cell infiltration and transcriptomic features. Moreover, multivariate Cox proportional hazard model was used to screen the key m6A regulators associated with the prognosis of ovarian cancer and we also constructed a four-gene signature for prognosis prediction through the last absolute shrinkage and selection operator (LASSO) Cox regression. The survival analysis curve and receiver operating characteristic (ROC) curve exhibited this risk-gene signature could be used as independent prognostic markers for ovarian cancer. In conclusion, m6A RNA methylation regulators are associated with the malignant progression of ovarian cancer and could be a potential in prognostic prediction and treatment for ovarian cancer.